Adenosine Triphosphate Prevents Serum Deprivation-Induced Apoptosis in Human Mesenchymal Stem Cells via Activation of the MAPK Signaling Pathways. (18th December 2014) - Berlier, Jessica L.; Rigutto, Sabrina; Dalla Valle, Antoine; Lechanteur, Jessica; Soyfoo, Muhammad S.; Gangji, Valerie; Rasschaert, Joanne
Abstract: Human mesenchymal stem cells (hMSC) are multipotent cells derived from various sources including adipose and placental tissues as well as bone marrow. Owing to their regenerative and immunomodulatory properties, their use as a potential therapeutic tool is being extensively tested. However, one of the major hurdles in using cell-based therapy is the use of fetal bovine serum that can trigger immune responses, viral and prion diseases. The development of a culture medium devoid of serum while preserving cell viability is therefore a major challenge. In this study, we demonstrated that adenosine triphosphate (ATP) restrained serum deprivation-induced cell death in hMSC by preventing caspases 3/7 activation and modulating ERK1/2 and p38 MAPK signaling pathways. We also showed that serum deprivation conditions triggered dephosphorylation of the proapoptotic protein Bad leading to cell death. Adjunction of ATP restored the phosphorylation state of Bad. Furthermore, ATP significantly modulated the expression of proapoptopic and antiapoptotic genes, in favor of an antiapoptotic profile expression. Finally, we established that hMSC released a high amount of ATP in the extracellular medium when cultured in a serum-free medium. Collectively, our results demonstrate that ATP favors hMSC viability in serum deprivation conditions. Moreover, they shed light on the cardinal role of the MAPK pathways, ERK1/2 and p38 MAPK, in promoting hMSC survival. Stem Cells   2015;33:211–218